P119 Picking up a bug by picking your nose hand to nose transmission of streptococcus pneumoniae in healthy participants – pilot study. (15th November 2017) - Connor, V; German, E; Robinson, R; Hales, C; Lowe, C; Zaisi, S; Adler, H; Lazarova, L; Hill, H; Wright, AD; Nikolaou, E; Pojar, S; et al.
Abstract : Introduction and Objectives: Streptococcus pneumoniae (pneumococcus) is a leading cause of morbidity and mortality worldwide, causing community acquired pneumonia (CAP), otitis media, bacterial meningitis and septicemia. Respiratory illnesses are reduced by handwashing, but for pneumococcus, the importance of non-aerosolised modes of spread is unknown. Our objective was to investigate the modes of transmission of S.pneumoniae from the hands to nose that are able to cause colonisation. Methods: This study examines "hand-to-nose" transmission using a modification of our established controlled human infection model: healthy volunteers were administered pneumococcus (serotype 6B) onto their fingertip or back of their hands in a wet or dry dot, and asked to either sniff the bacterial residue, or make direct contact with the nasal mucosal surface (pick/poke their nose). Colonisation was defined as pneumococcal culture at any time point between day 2 and 9 post exposure. Results: Colonisation rates were highest in those participants who poked their nose with wet pneumococcus ('wet poke group' 4/10, 40%), and who sniffed the wet bacteria from the back of the hand ('wet sniff group' 3/10, 30%). Drying of the bacteria on the skin before "sniff" or "poke" was associated with low colonisation rates (1/10 and 0/10 respectively). The 'wet sniff' technique was further investigated to improve precision of rates, extending the group to 33 participants, of which 6 were positive (18%). Conclusion: We have shown that hands can be vehicles for transmission of Streptococcus pneumoniae and that wet particles increased transmission. This reinforces the imperative for good hand hygiene especially in populations at risk of invasive pneumococcal disease or pneumonia such as young children, elderly and immunosuppressed people